The generation of scenes in mixed reality environments using the chromakey technique - Sanches, Silvio Ricardo Rodrigues; Sementille, Antonio Carlos [UNESP]; Rodello, Ildelberto Aparecido; Brega, José Remo Ferreira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
A classic problem in the development of Mixed Reality systems is the registration. The correct alignment between virtual objects and the real elements is extremely important for the coherent composition of the resultant scene. Considering this context, this paper describes an approach for the composition of scenes in Mixed Reality environments using the chromakey technique for the extraction of real objects. After that, the scene is mounted in a coherent way related to the depth in OpenGL framebuffer for posterior rendering. ©2007 IEEE.
Keywords: International conferences; Mixed reality; Mixed reality systems; Real objects; Virtual objects; Virtual reality